DIAGNOSIS OF BRAKE SYSTEMS OF MOTOR VEHICLES IN OPERATING CONDITIONS - Rasul V. Huseynov; Karina A. Alieva; Madina N. Nazhmudinova (International Journal of Advanced Studies, 2022)
The article analyzes the effectiveness of methods for monitoring motor vehicles during operation. The relevance of the study lies in the fact that the braking system is an important element responsible for the safe operation of the car.